Surgical Excision of Duodenal/Pancreatic Metastatic Renal Cell Carcinoma - Espinoza, Eduardo; Hassani, Ali; Vaishampayan, Ulka; Shi, Dongping; Pontes, J. Edson; Weaver, Donald W. (Frontiers in Oncology, 2014)
Renal cell carcinoma (RCC) has a potential to metastasize to almost any site and this may occur many years following nephrectomy. We present 6 cases with uncommon sites of metastasis: 4 patients presented with distal pancreatic metastasis and 2 with duodenal/head of the pancreas metastasis. Time to metastatic disease varied from 1 to 19 years following renal surgery. For patients are alive and 2 succumbed to their disease. Long-term survival can be achieved with aggressive surgical excision of disease.